2009
DOI: 10.5713/ajas.2010.60150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Level of Dietary Inorganic and Organic Copper and Energy Level on the Performance and Nutrient Utilization of Broiler Chickens

Abstract: An experiment was conducted to determine the influence of dietary inorganic (copper sulfate) and organic (copper proteinate) forms of copper and energy level on performance and nutrient utilization of broiler chickens. Two hundred day-old commercial Vencobb broiler chicks were purchased and randomly distributed to 20 cages of 10 birds each. These replicates were randomly assigned to one of five treatments in a ((2×2)+1) factorial arrangement. These two factors were sources of Cu (CuSO 4 vs. Cuproteinate) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…The present results agree with the findings of Balevi and Coskun (2004), Luo et al (2005), Aksu et al (2011), and Samanta et al (2011), who indicated that dietary supplementation of birds with organic or inorganic copper led to a significant decrease in feed consumption when compared with the control group. On the other hand, these results are in contrast with the other findings of Banks et al (2004), Lim and Paik (2006) and Das et al (2010), who found that dietary supplementation of birds with copper organic or inorganic copper had no significant effect on feed consumption when compared with the control group.…”
Section: Whole Experimental Periodcontrasting
confidence: 99%
See 3 more Smart Citations
“…The present results agree with the findings of Balevi and Coskun (2004), Luo et al (2005), Aksu et al (2011), and Samanta et al (2011), who indicated that dietary supplementation of birds with organic or inorganic copper led to a significant decrease in feed consumption when compared with the control group. On the other hand, these results are in contrast with the other findings of Banks et al (2004), Lim and Paik (2006) and Das et al (2010), who found that dietary supplementation of birds with copper organic or inorganic copper had no significant effect on feed consumption when compared with the control group.…”
Section: Whole Experimental Periodcontrasting
confidence: 99%
“…The current results harmonize with the results obtained by experimental work of Das et al (2010), who noticed that feed conversion ratio improved with when the diet was supplemented copper proteinate as compared to copper sulfate. This effect is due to high content of healthy conditions of birds fed copper.…”
Section: Whole Experimental Periodsupporting
confidence: 90%
See 2 more Smart Citations
“…Mintrex ® Cu is a chelated source of copper that contains a minimum of 17% copper and 78% hydroxy methionine analog (2‐hydroxy‐4‐methylthiobutanoic acid, HMTBa). Mintrex ® Cu has been shown to be a bioavailable copper source, comparable to a traditionally used inorganic source of copper in chickens (Das et al 2010). Mintrex ® Cu shows the same pattern as copper sulfate in increasing liver copper content in chickens for fattening when added to a basal diet in supplementations between 10 and 500 mg/kg diet.…”
mentioning
confidence: 99%